MATERNITY LEAVE DISCOURSE – SOCIAL NETWORK ANALYSIS - Ahmad Nizar Yogatama (Program Sarjana Manajemen Universitas Internasional Batam, 2023)
Some countries have different regulations related to this maternity leave. female workers have the right to get maternity leave rations for 1.5 months before giving birth and 1.5 months after giving birth and still get full salary. Some cases in the field have different combinations, but the allotment of maternity leave given is three months. The methods used in this study are text mining and social network analysis. Text mining is used to see frequently appearing words related to maternity leave as well as twitter users' responses related to the word, while social network analysis is used to see what the female workforce really wants related to maternity leave policies. Based on the purpose of this research, there are 3 words that often appear, namely paid, sick and paternity. Most tweets that exist, have neutral and positive sentiment. However, what needs to be of particular concern in the future is that the implementation of this policy on maternity leave can be beneficial for both parties, namely workers and employers.